Synergistic effect between ammonium polyphosphate and expandable graphite on flame-retarded poly(butylene terephthalate). (23rd February 2018) - Zhang, Weizhou; Ren, Jiawei; Wei, Ting; Guo, Weihong
Abstract: In this paper, the synergistic effect of ammonium polyphosphate (APP) and expandable graphite (EG) on flame-retarded poly(butylene terephthalate) (PBT) was systermically investigated using limiting oxygen index (LOI), UL-94 testing, microscale combustion calorimetry (MCC), thermal-gravimetric analysis (TGA) and scanning electronic microscopy (SEM). PBT composites containing 20 wt% of APP: EG (1:3) combinations exhibits a high LOI value of 29.8 and reaches V-0 rating in UL-94 testing, indicating that the flame retardant property is greatly enhanced compared to the composites solely with APP or EG. SEM images show that the combination of APP and EG could promote the formation of a compact char layer. The compact char layer protects the PBT resin efficiently by preventing penetration of heat flux inside the matrix and retards the decomposition of PBT, consequently improves the thermal stability of PBT materials as revealed by TGA. All of the results demonstrate that APP and EG are high efficiency synergists for improving the flame retardation of PBT materials.